2004
DOI: 10.1002/er.1012
|View full text |Cite
|
Sign up to set email alerts
|

Diffused introduction of Organic Rankine Cycle for biomass-based power generation in an industrial district: a systems analysis

Abstract: Specific Organic Rankine Cycle (ORC) units dedicated to biomass-based power production have recently been developed through the introduction of novel organic working media and technology innovation. For small systems, ORC technology appears as an efficient alternative to conventional generation if also process waste heat can be exploited, as resulted in the last few years from the successful operation of several demonstration plants in Austria and Switzerland. The present study aims to investigate the impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…Efficiencies and ratios have been derived from the literature (Chinese et al, 2004;Pantaleo et al, 2013), considering the size classes defined in the model, and are reported in Table 5.…”
Section: Technology Options and System Boundariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Efficiencies and ratios have been derived from the literature (Chinese et al, 2004;Pantaleo et al, 2013), considering the size classes defined in the model, and are reported in Table 5.…”
Section: Technology Options and System Boundariesmentioning
confidence: 99%
“…The ORC cost function is derived from previous studies (Chinese et al, 2004), while costs of anaerobic digesters (ADs), including civil works and of internal combustion engines are obtained as a least squares interpolation of data gathered from constructors and reported in Figure 5.…”
Section: Cost Estimationmentioning
confidence: 99%
“…In this work the various technological options examined apply solely to the base-load device, whereas the peak-load biomass boiler characteristics remain the same in all scenarios. In all cases, a centralized power plant is considered, as it has been suggested by [8] that distributed cogeneration appears to be less efficient. The heating and cooling generated is transferred via a district energy network to the final consumers.…”
Section: Model Descriptionmentioning
confidence: 99%
“…District heating combined with CHP has been used for many years now, but lately the shift towards biomass-powered CHP is apparent. Biomass CHP with district heating has not been considered a viable option for areas with warm climate up to now, as in these areas traditional cogeneration applications tend to prove financially unviable, due to the short operational time within the year [8]. It is interesting to note that the British Energy Efficiency Office has recommended that a CHP system should run for a minimum of 4500 h per annum to be financially viable [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation